Literature Review: Model Penerapan Ekologi Untuk Menjaga Kesehatan Mental - Mas Rukhin Lubabul Huda (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2025)
This research aims to deepen and analyze the various types of ecological application models to maintain mental health in society. Ecology has a role not only in biological health but also in mental health in humans. This research method uses a qualitative research approach. LR (Literature Review) with primary source data, namely research articles for the period 2021-2025, the data collection technique uses the application Publish or Perish by using keywords "ekologi"dan"Kesehatan mental", then the researcher went deeper to discuss it further and found 7 research articles. The results of research on various models of applying ecology that can help a person's mental health are: providing a green concept in sports venues, gardening, creating city parks, creating recreational areas with a concept of lots of plants, providing an understanding of healthy city planning to children, planting trees, and counseling activities for playing in nature in educational institutions. The benefit of this research is that the wider community is able to maintain ecology well because the role of ecology in humans, especially, is an important role in maintaining a person's mental health, in addition to that, with the development of the times, plants are starting to be replaced by industrial plants so that it is very important to maintain the plant ecosystem so that the environment remains stable.